CHAN DIAGNOSTIC PLOT APPLICATION FOR WATER CONING IDENTIFICATION IN MULTILAYER RESERVOIRS - Herdiansyah, Gilang
This study evaluates the use of the Chan Plot diagnostic technique to identify water production mechanisms, particularly water coning, in Indonesian oil fields. Excessive water production due to water coning and channeling is a major challenge in oil production operations, which can reduce well productivity and increase operating costs. Using CMG software simulations, the Chan Plot was applied to reservoir models with various layer configurations, including multilayer reservoirs. The results indicate that the Chan Plot can effectively identify water coning in reservoirs with one or two layers, where a negative slope in the WOR' graph indicates this phenomenon. However, in reservoirs with three layers, the method shows limitations, as the diagnostic results indicate the presence of channeling in one layer, even though water coning is still detected overall. Additionally, increased reservoir permeability was found to impact flow rate and pressure gradient around the well, affecting the WOR' slope value and accelerating water coning. The study concludes that while the Chan Plot is effective under simple conditions, it may require adjustments or additional diagnostics for more complex reservoir conditions.Keywords: low salinity water injection (LSWI), water alternating gas (WAG), cation exchange capacity (CEC), oil recovery, tapered WAG, constant WAG, hybrid WAG.